2018
DOI: 10.9775/kvfd.2018.20329
|View full text |Cite
|
Sign up to set email alerts
|

Hayvansal Yağın Yağ Asitleri Kalsiyum Tuzunun Broyler Performansı, İç Yağın Yağ Asidi Kompozisyonu, Kemiklerin Biyomekanik Özellikleri ve Tibia Mineral Düzeyi Üzerine Etkisi

Abstract: This study evaluated the effects of a graded concentration of dietary calcium soaps of tallow (CST) supplementation on broiler performance, carcass characteristics, abdominal fat fatty acid profile, bone biomechanical properties, and bone mineral composition. One hundred and forty 11-d-old male broiler chickens were randomly allocated to 4 experimental groups with 5 replicate pens containing 7 birds per each. The birds received cornsoybean meal based diet and CST (CST0, CST10, CST20, and CST30, respectively) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…These findings reported that supplementation of BSFLO-SCa increased FCR, which is associated with decreased of FI and BWG with supplementation of BSFLO-SCa. These finding supported the observation of Çalik et al (2019) , who reported that calcium salt tallow ( CST ) increased FCR compared with control that caused by decreased of FI and BWG with the increased of level supplementation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings reported that supplementation of BSFLO-SCa increased FCR, which is associated with decreased of FI and BWG with supplementation of BSFLO-SCa. These finding supported the observation of Çalik et al (2019) , who reported that calcium salt tallow ( CST ) increased FCR compared with control that caused by decreased of FI and BWG with the increased of level supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the problem with using liquid fat in developing countries is the need for proper facilities for mixing with solid feedstuff. Calcium salt form of fatty acids is a saponification process that may alleviate this problem, easy to handle ( Abd-ElhayGado and Elsebaai, 2017 ; Shahryari et al, 2021 ), higher stability and resistant to oxidation ( Çalik et al, 2019 ; Villanueva-Lopez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…After bone measurements, tibia samples were defatted in chloroform and methanol (2:1) for 72 h (Çalık et al., 2019 ). Subsequently, tibia samples were dried for 12 h at 105°C and ashed overnight at 600°C to determine dry matter and ash percentage, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After bone measurements, bone samples were defatted in chloroform and methanol (2:1) for 72 h for mineral analysis (Çalık et al, 2019). The concentrations of iron, zinc, potassium, calcium, phosphorus, magnesium and manganese in shell, yolk, albumen, yolk sac and bones were determined as in the feed.…”
Section: Methodsmentioning
confidence: 99%